Drug‐induced aseptic meningitis: 329 cases from the French pharmacovigilance database analysis - Bihan, Kevin (Br J Clin Pharmacol, 2019)
AIMS: Drug‐induced aseptic meningitis (DIAM) is an adverse drug reaction of exclusion; only few studies have addressed this iatrogenic disease. The aim was to characterize DIAM and to identify suspected drugs. METHODS: Data were collected from the analysis of the French Pharmacovigilance Database from inception (1 January 1985) to 8 March 2017. All cases were initially analysed according to the French imputability method by institutional pharmacologists (clinicians or pharmacists). Further analyses of well documented cases were then performed. RESULTS: In this study, 329 cases of aseptic meningitis were retrieved from the French Pharmacovigilance Database for a total of 429 suspected drugs. Analysis of 203 well documented cases, including 282 drugs, showed that the main reported classes were intravenous polyvalent immunoglobulin, nonsteroidal anti‐inflammatory drugs (NSAIDs), vaccines, antimicrobials, intrathecal antimetabolites, corticosteroids and antalgics/anaesthetics (except NSAIDs). Lymphocytic (33.0%) and purulent (44.8%) meningitis represented the majority of cases of aseptic meningitis. In other cases, the cerebrospinal fluid was mixed (45–55% of neutrophils +45–55% of lymphocytes) or data about cerebrospinal fluid composition were lacking. Most DIAM cases (96%) had a favourable reported outcome with full recovery or minimal residual symptoms. CONCLUSION: The most frequently involved drugs in DIAM were intravenous polyvalent immunoglobulin, NSAIDs, vaccines, and antimicrobials and this without being able to differentiate them in terms of biological characteristics. Although further studies are needed to better understand the pathophysiological mechanisms of DIAM, a continuous enrichment of pharmacovigilance databases is essential to identify new signals and to help clinicians in the understanding of DIAM.